Peran Mediasi Motivasi Kerja Dalam Pengaruh Kompensasi terhadap Semangat Kerja: Penelitian - A.A. Ngurah Bagus Danendra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Compensation and motivation play an important role in increasing employee morale. The purpose of this study was to determine the effect of compensation on employee morale and the role of motivation in mediating the effect of compensation on employee morale. The study was conducted on employees of PT. Amanaid with a total of 40 employees. The respondents of the study were determined using a saturated sampling method. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 11 indicators. The data analysis technique used was path analysis. The test results showed that compensation had a positive and significant effect on morale, compensation had a positive and significant effect on motivation and motivation had a positive and significant effect on employee morale. The limitations of this study are that the location of the study is only within the scope of PT. Amanaid so that the results of this study cannot explain the situation in other companies other than PT. Amanaid.